Improving the Health of Communities through Population Health Assessments - Deprez, Ron; Manchester, Chloe (Maine Policy Review, 2018)
This paper describes a comprehensive, science-based approach for conducting a population health assessment (PHA), a process for identifying upstream nonmedical, social and economic determinants of health in a community, including risk factors associated with poor health status. A PHA focuses on diagnosing and improving population health disparities using public, private, and community-based strategies and resources. The paper traces the evolution of PHAs from community health needs assessments and community benefits planning. It describes the PHA process, methods, data, and analytical techniques that permit the identification of specific underlying factors in a community that adversely affect health. It also suggests criteria to prioritize health issues and strategies that help communities implement sustainable policy, infrastructure, or services improvements.